Brazil burning! What is the potential impact of the Amazon wildfires on vector-borne and zoonotic emerging diseases? - A statement from an international experts meeting (2019)
http://scienti.colciencias.gov.co:8081/cvlac/visualizador/generarCurriculoCv.do?cod_rh=0000153095